Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass
By using the combination of Ag-NiCr alloy functional layer and nickel-chromium absorption layer in high-transmissive low-radiation coated glass, combined with specific heat treatment conditions, the existing high-transmissive low-radiation coated glass has been solved, and a higher transmittance, lower reflectivity and more stable color effect is achieved.
Patent Information
- Application Number
- CN202411754219.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing high-transmittance low-radiation coating glass has problems such as low visible light transmittance, high internal reversal, and large color changes before and after tempering, resulting in poor customer experience and low processing yield.
Ag-NiCr alloy is highly transparent and tempered low-emission coating glass, and by sequentially plating the silicon nitride dielectric layer, seed protective layer, nickel-chromium absorbing layer, Ag-NiCr alloy functional layer, nickel-chromium absorbing layer, seed protective layer and silicon nitride dielectric layer on the glass substrate, the high strength and corrosion resistance of nickel-chromium materials are used to form an Ag-NiCr alloy material layer with significantly reduced grain diameter through heat treatment under specific conditions.
It significantly improves the wear resistance, corrosion resistance and high temperature resistance of the film layer, improves the processing resistance of the coated glass, and achieves the effects of high visible light transmittance, low indoor reflectivity and small color differences before and after tempering, which is suitable for large-scale promotion and application.
Smart Images

Figure CN119638212A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of coated glass, and in particular to an Ag-NiCr alloy high-transmittance temperable low-radiative coated glass. Background Art
[0002] With the continuous advancement of the country's "zero carbon" strategy, Low-e glass is an important material for achieving building energy conservation and reducing carbon emissions at this stage and in the future, and it is also the most competitive product in the building customized door and window decoration industry.
[0003] Currently, customers in the market have a high preference for high-transmittance, low-emissivity customized doors and windows, but most of the existing high-transmittance, low-emissivity coated glass products have the defects of poor processing resistance, high indoor reflection, poor customer experience, and low glass processing yield.
[0004] Chinese patent CN101767939A discloses a high-transmittance tempered low-emissivity coated glass, which improves the mechanical properties of Low-E glass by coating an anti-reflection film layer, a high-temperature flame-retardant film layer, a metal isolation film layer, a low-emissivity functional film layer, a metal isolation film layer, an anti-reflection film layer, a high-temperature flame-retardant film layer and a protective layer on the glass substrate in sequence. Although the coated glass improves the mechanical properties of the film layer and reduces the risk of scratches through the design of the protective functional layer, it restricts the appearance color of the film layer, has a certain impact on the beauty of the building, reduces the customer experience, and is not conducive to large-scale application.
[0005] Chinese patent CN201842773U discloses a silver-gray high-brightness low-radiation coated glass, which is coated with silicon nitride film, titanium oxide film, silver film, nickel-chromium film, tin oxide film, titanium oxide film, and silicon nitride film on the surface of the glass substrate from the bottom layer to the top, forming a seven-layer film structure of silver-gray high-transmittance low-radiation coated glass. This coated glass not only takes advantage of the high refractive index of the titanium oxide film, but also takes advantage of the small amount of oxidized nickel-chromium film to block less visible light, and produces a low-radiation coated glass with an elegant silver-gray color and high visible light transmittance; although the appearance is guaranteed, the processing resistance is poor, the film layer is complex, and the internal reflection is high, which does not meet the requirements of customized products.
[0006] Chinese patent CN202608166U discloses a reinforced single silver high-transmittance low-emissivity coated glass that can be processed remotely. The coated glass is coated with a first dielectric layer, a second dielectric layer, a first protective layer, an Ag layer, a second protective layer, a third dielectric layer, a fourth dielectric layer and a fifth dielectric layer in sequence on a glass substrate; it has the effect of being processable remotely, belongs to a reinforced single silver low-emissivity coated glass, and has a visible light transmittance of about 79% after tempering; however, the coated glass has the problems of complex dielectric layer, high processing cost, and large color change after tempering.
[0007] It can be seen that based on the above-mentioned problems existing in the existing high-transmittance low-emissivity coated glass, it is urgent to develop a tempered low-emissivity coated glass with high visible light transmittance, low internal reflection, good appearance color and excellent processability. Summary of the invention
[0008] The purpose of the invention is to propose an Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass in view of the defects of the existing high-transmittance low-emissivity coated glass, such as low visible light transmittance, high internal reflection and large color change before and after tempering.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on the surface of the glass substrate; wherein the film layer comprises, from the glass substrate outward, a first silicon nitride dielectric layer with a thickness of 20-30 nm, a second seed protection layer with a thickness of 10-15 nm, a third nickel-chromium absorption layer with a thickness of 1-2 nm, a fourth Ag-NiCr alloy functional layer with a thickness of 7-12 nm, a fifth nickel-chromium absorption layer with a thickness of 1-2 nm, a sixth seed protection layer with a thickness of 5-10 nm, and a seventh silicon nitride dielectric layer with a thickness of 30-50 nm;
[0011] Wherein, the fourth Ag-NiCr alloy functional layer is formed in a vacuum degree not less than 5*10 -6 In a vacuum environment of mbar, a first silver layer with a thickness of 3-5 nm, a nickel-chromium partition layer with a thickness of 1-2 nm and a second silver layer with a thickness of 3-5 nm, which are sequentially magnetron sputtered, are heat treated at a temperature of 680-720°C for 5-8 min, and the prepared alloy material layer is cooled at a cooling rate of 60-80°C / min.
[0012] The invention discloses an Ag-NiCr alloy high-transmittance temperable low-radiation coated glass. Not only does the nickel-chromium absorption layer in the film layer wrap the functional layer, but also the nickel-chromium material has the advantages of high strength, corrosion resistance and high temperature resistance, so as to improve the wear resistance and corrosion resistance of the film layer. Moreover, the nickel-chromium material is added to the silver layer for segmentation, and through heat treatment under specific conditions, atoms in the silver layer and the nickel-chromium segmentation layer are mutually infiltrated and diffused, and fully fused to form an Ag-NiCr alloy material layer with significantly reduced grain diameter, thereby improving the hardness, wear resistance, corrosion resistance and high temperature resistance of the functional layer, and significantly improving the processing resistance of the film layer. The coated glass has the advantages of simple structure, high visible light transmittance, low indoor reflectivity and small color difference before and after tempering, and is suitable for large-scale promotion and application.
[0013] Among them, preferably, the second seed protective layer is a zinc oxide layer or a titanium oxide layer; the preferred protective layer material has better bonding strength between film layers and can better protect the functional layer without affecting the optical properties of the film layer material.
[0014] Among them, preferably, the sixth seed protective layer is an AZO layer; the preferred protective layer material has better bonding strength between film layers and can better protect the functional layer without affecting the optical properties of the film layer material.
[0015] Preferably, when the fourth Ag-NiCr alloy functional layer is prepared by magnetron sputtering coating and heat treatment, the vacuum degree of the vacuum environment is not less than 3*10 -6 mbar; the preferred vacuum environment can prevent the Ag-NiCr alloy material from being oxidized and enhance the adhesion of the film layer, so that the fourth Ag-NiCr alloy functional layer has better optical properties.
[0016] Preferably, the heat treatment temperature is 690-700°C, the time is 5-6min, and the cooling rate is 60-80°C / min; with the preferred heat treatment condition parameters, the grain size of the obtained Ag-NiCr alloy is more uniform, and the optical properties of the fourth Ag-NiCr alloy functional layer are better.
[0017] Preferably, the thickness of the first silicon nitride dielectric layer is 22-28 nm; with the preferred thickness, the film layer has better bonding strength on the glass substrate, which is beneficial to improving the toughening resistance of the coated glass.
[0018] Preferably, the thickness of the second seed protection layer is 11-13 nm; the preferred thickness has better protection effect and higher visible light transmittance.
[0019] Preferably, the thickness of the fourth Ag-NiCr alloy functional layer is 8-10 nm; the preferred thickness does not reduce the emissivity, and the film layer has better visible light transmittance and lower indoor reflectivity.
[0020] Preferably, the thickness of the sixth seed protection layer is 6-8 nm; the preferred thickness has better protection effect and higher visible light transmittance.
[0021] Preferably, the thickness of the seventh silicon nitride dielectric layer is 35-45 nm; with the preferred thickness, the coated glass has a more beautiful appearance color while having a better visible light transmittance.
[0022] The Ag-NiCr alloy high-transmittance tempered low-radiation coated glass of the present invention can be prepared by magnetron sputtering coating technology, which is formed by sequentially coating and heat-treating under a high vacuum background. The preparation method is simple, mature and suitable for industrial production. The coated glass can achieve a good appearance effect and can better meet the lighting, aesthetic and energy-saving requirements of buildings.
[0023] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0024] 1. The Ag-NiCr alloy high-transmittance temperable low-radiation coated glass of the present invention has a visible light transmittance of not less than 80% after tempering on a 6 mm ordinary float glass, good lighting effect, neutral transmission color, low indoor reflectivity, small color difference before and after tempering, good indoor and outdoor sensory effects, and no color cast on the front and side. The specific optical parameters are as follows:
[0025]
[0026] Note: In order to quantitatively describe and measure color, the CIE1976L*a*b* color space is generally used internationally to measure color: L or R is generally used to indicate brightness, and there is a certain conversion relationship between the two. The value is in the range of 0-100, and the larger the value, the higher the brightness; a* is used to indicate redness and greenness, a negative a* indicates green, a positive a* indicates red, and the larger the absolute value, the greater the degree of green or red; b* is used to indicate yellowness and blueness, a negative b* indicates blue, a positive b* indicates yellow, and the larger the absolute value, the greater the degree of yellow or blue; the closer a* and b* are to zero, the more neutral the transmitted color is; T indicates transmittance, and the larger the number, the higher the transmittance.
[0027] 2. The Ag-NiCr alloy high-transmittance tempered low-emissivity coated glass of the present invention is prepared by adding nickel-chromium material to the silver layer for segmentation, and by heat treatment under specific conditions, so that atoms in the silver layer and the nickel-chromium segmentation layer penetrate and diffuse with each other, and fully fuse to form an Ag-NiCr alloy material layer with significantly reduced grain diameter, thereby significantly improving the optical properties of the film layer, and can significantly improve the emissivity and light-to-heat ratio of the coated glass when the thickness of the film layer remains unchanged.
[0028] 3. The Ag-NiCr alloy high-transmittance temperable low-radiation coated glass of the present invention has the advantages of simple structure, high visible light transmittance, low indoor reflectivity and small color difference before and after tempering, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 1 is a schematic structural diagram of the Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass in Example 1 of the present invention;
[0030] Figure 2This is an electron microscope scanning image of the functional layer in Example 1 of the present invention;
[0031] Figure 3 This is a scanning electron microscope image of the functional layer in Comparative Example 1 of the present invention.
[0032] Markings in the figure: 1-glass substrate; 2-film layer; 201-first silicon nitride dielectric layer; 202-second seed protection layer; 203-third nickel-chromium absorption layer; 204-fourth Ag-NiCr alloy functional layer; 205-fifth nickel-chromium absorption layer; 206-sixth seed protection layer; 207-seventh silicon nitride dielectric layer. DETAILED DESCRIPTION
[0033] The present invention will be described in detail below in conjunction with the accompanying drawings.
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] Example 1
[0036] A Ag-NiCr alloy high-transmittance tempered low-radiation coated glass (structure such as Figure 1 ), comprising a glass substrate and a film layer, wherein the film layer is arranged on a surface of the glass substrate; wherein the film layer comprises, from the glass substrate outwards, a first silicon nitride dielectric layer with a thickness of 30 nm, a second seed protection layer (zinc oxide layer) with a thickness of 10 nm, a third nickel-chromium absorption layer with a thickness of 1 nm, a fourth Ag-NiCr alloy functional layer with a thickness of 10 nm, a fifth nickel-chromium absorption layer with a thickness of 1 nm, a sixth seed protection layer (AZO layer) with a thickness of 10 nm, and a seventh silicon nitride dielectric layer with a thickness of 35 nm;
[0037] The fourth Ag-NiCr alloy functional layer is sequentially placed in a vacuum environment (vacuum degree 3*10 -6 mbar), a first silver layer with a thickness of 4.5 nm, a nickel-chromium partition layer with a thickness of 1 nm, and a second silver layer with a thickness of 4.5 nm were heat treated at a temperature of 690° C. for 5.5 min, and then cooled at a cooling rate of 70° C. / min to form an alloy material layer.
[0038] Example 2
[0039] A Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on the surface of the glass substrate; wherein the film layer comprises, from the glass substrate outward, a first silicon nitride dielectric layer with a thickness of 30 nm, a second seed protection layer (titanium oxide layer) with a thickness of 10 nm, a third nickel-chromium absorption layer with a thickness of 2 nm, a fourth Ag-NiCr alloy functional layer with a thickness of 7 nm, a fifth nickel-chromium absorption layer with a thickness of 2 nm, a sixth seed protection layer (AZO layer) with a thickness of 5 nm, and a seventh silicon nitride dielectric layer with a thickness of 30 nm;
[0040] The fourth Ag-NiCr alloy functional layer is sequentially placed in a vacuum environment (vacuum degree 5*10 -6 mbar), a first silver layer with a thickness of 3 nm, a nickel-chromium partition layer with a thickness of 1 nm, and a second silver layer with a thickness of 3 nm were plated at a temperature of 720° C. for 5 min, and then cooled at a cooling rate of 80° C. / min to form an alloy material layer.
[0041] Example 3
[0042] A Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on the surface of the glass substrate; wherein the film layer comprises, from the glass substrate outward, a first silicon nitride dielectric layer with a thickness of 22 nm, a second seed protection layer (titanium oxide layer) with a thickness of 11 nm, a third nickel-chromium absorption layer with a thickness of 1 nm, a fourth Ag-NiCr alloy functional layer with a thickness of 12 nm, a fifth nickel-chromium absorption layer with a thickness of 2 nm, a sixth seed protection layer (AZO layer) with a thickness of 8 nm, and a seventh silicon nitride dielectric layer with a thickness of 45 nm;
[0043] The fourth Ag-NiCr alloy functional layer is sequentially placed in a vacuum environment (vacuum degree 5*10 -6 mbar), a first silver layer with a thickness of 5 nm, a nickel-chromium partition layer with a thickness of 2 nm, and a second silver layer with a thickness of 5 nm were heat treated at a temperature of 700° C. for 6 min, and then cooled at a cooling rate of 75° C. / min to form an alloy material layer.
[0044] Example 4
[0045] A Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on the surface of the glass substrate; wherein the film layer comprises, from the glass substrate outward, a first silicon nitride dielectric layer with a thickness of 28 nm, a second seed protection layer (zinc oxide layer) with a thickness of 13 nm, a third nickel-chromium absorption layer with a thickness of 2 nm, a fourth Ag-NiCr alloy functional layer with a thickness of 8 nm, a fifth nickel-chromium absorption layer with a thickness of 1 nm, a sixth seed protection layer (AZO layer) with a thickness of 6 nm, and a seventh silicon nitride dielectric layer with a thickness of 50 nm;
[0046] The fourth Ag-NiCr alloy functional layer is sequentially placed in a vacuum environment (vacuum degree 4*10 -6 mbar), a first silver layer with a thickness of 3 nm, a nickel-chromium partition layer with a thickness of 2 nm, and a second silver layer with a thickness of 3 nm were plated at a temperature of 680° C. for 8 min, and then cooled at a cooling rate of 60° C. / min to form an alloy material layer.
[0047] Comparative Example 1
[0048] A low-emissivity coated glass comprises a glass substrate and a film layer, wherein the film layer is arranged on the surface of the glass substrate; wherein the film layer comprises, from the glass substrate outwards, in sequence a first silicon nitride dielectric layer with a thickness of 30 nm, a second seed protection layer (zinc oxide layer) with a thickness of 10 nm, a third nickel-chromium absorption layer with a thickness of 1 nm, a fourth Ag functional layer with a thickness of 10 nm, a fifth nickel-chromium absorption layer with a thickness of 1 nm, a sixth seed protection layer (AZO layer) with a thickness of 10 nm, and a seventh silicon nitride dielectric layer with a thickness of 35 nm.
[0049] The fourth Ag functional layer is in a vacuum environment (vacuum degree 3*10 -6 mbar), and after heat treatment at 690° C. for 5.5 min, the prepared material layer was cooled at a cooling rate of 70° C. / min.
[0050] Comparative Example 2
[0051] A low-emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on the surface of the glass substrate; wherein the film layer comprises, from the glass substrate outwards, a first silicon nitride dielectric layer with a thickness of 30 nm, a second seed protection layer (zinc oxide layer) with a thickness of 10 nm, a third nickel-chromium absorption layer with a thickness of 2 nm, a fourth Ag functional layer with a thickness of 7 nm, a fifth nickel-chromium absorption layer with a thickness of 2 nm, a sixth seed protection layer (AZO layer) with a thickness of 5 nm, and a seventh silicon nitride dielectric layer with a thickness of 30 nm;
[0052] Among them, the fourth Ag functional layer is in a vacuum environment (vacuum degree 3*10 -6 mbar), was subjected to heat treatment at 720° C. for 5 min, and then the prepared material layer was cooled at a cooling rate of 70° C. / min.
[0053] Comparative Example 3
[0054] A low-emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on a surface of the glass substrate; wherein the film layer comprises, from the glass substrate outward, a first silicon nitride dielectric layer with a thickness of 22 nm, a second seed protection layer (titanium oxide layer) with a thickness of 11 nm, a third nickel-chromium absorption layer with a thickness of 1 nm, a fourth Ag functional layer with a thickness of 12 nm, a fifth nickel-chromium absorption layer with a thickness of 2 nm, a sixth seed protection layer (AZO layer) with a thickness of 8 nm, and a seventh silicon nitride dielectric layer with a thickness of 45 nm;
[0055] The fourth Ag functional layer is in a vacuum environment (vacuum degree 3*10 -6 mbar), was subjected to heat treatment at 690° C. for 5.5 min, and then the prepared material layer was cooled at a cooling rate of 70° C. / min.
[0056] Comparative Example 4
[0057] A Ag-NiCr alloy high-transmittance tempered low-radiation coated glass (structure such as Figure 1 As shown), comprising a glass substrate and a film layer, wherein the film layer is arranged on the glass substrate surface; wherein the film layer comprises, from the glass substrate outward, a first silicon nitride dielectric layer with a thickness of 28 nm, a second seed protection layer (zinc oxide layer) with a thickness of 13 nm, a third nickel-chromium absorption layer with a thickness of 2 nm, a fourth Ag functional layer with a thickness of 8 nm, a fifth nickel-chromium absorption layer with a thickness of 1 nm, a sixth seed protection layer (AZO layer) with a thickness of 6 nm, and a seventh silicon nitride dielectric layer with a thickness of 50 nm;;
[0058] The fourth Ag functional layer is in a vacuum environment (vacuum degree 3*10 -6 mbar), was subjected to heat treatment at 680°C for 8 min, and then the prepared material layer was cooled at a cooling rate of 70°C / min.
[0059] Experimental Example 1: Grinding and penetration test after tempering
[0060] After the coated glass in Examples 1-4 and Comparative Examples 1-4 was tempered (tempering temperature was 700° C.), it was ground by a grinder for 200 revolutions, and the visible light transmittance was tested. The results are shown in Table 1:
[0061] Table 1 Transmittance results after tempering and grinding for 200 revolutions
[0062]
[0063] From the analysis of the experimental results in Table 1, it can be seen that the coated glasses in Examples 1-4 of the present invention have better wear resistance.
[0064] Experimental Example 2: After the coated glasses in Examples 1-4 and Comparative Examples 1-4 were tempered (tempering temperature was 700°C), anti-oxidation (the shortest time required for exposure to air for oxidation) and acid and alkali resistance tests (after soaking in 10% hydrochloric acid and 10% sodium hydroxide solution for 24 hours, the visible light transmittance was tested). The results are shown in Table 2:
[0065] Table 2 Antioxidation and acid and alkali resistance test results
[0066]
[0067] From the analysis of the experimental results in Table 2, it can be seen that the coated glass in Examples 1-4 of the present invention has better anti-oxidation effect and corrosion resistance effect.
[0068] Experimental Example 3: Comparative Experiment on Appearance Color and Performance Before and After Tempering
[0069] The coated glasses in Examples 1-4 and Comparative Examples 1-4 were tempered (tempering temperature was 700° C.), and the appearance color, indoor reflectivity, transmittance, and emissivity of the coated glasses before and after tempering were tested. The results are shown in Table 3:
[0070] Table 3 Performance change data of coated glass before and after tempering
[0071]
[0072]
[0073] From the experimental results in Table 3, it can be seen that the coated glass in Examples 1-4 of the present invention has higher transmittance, lower indoor reflection, neutral transmittance color, more comfortable appearance, better performance, and smaller changes in various properties after tempering treatment than that in Comparative Examples 1-4.
[0074] Experimental Example 4: Grain Intercept Estimation
[0075] The functional layers of the coated glasses (before tempering) in Examples 1-4 and Comparative Examples 1-6 were scanned by SEM scanning electron microscope (wherein the functional layer scanning diagram of Example 1 is shown in FIG. Figure 2 , the functional layer scanning head of comparative example 1 is shown in Figure 3), and estimated the average intercept of the grains, the results are shown in Table 4:
[0076] Table 4 Average intercept of grains in functional layer
[0077] Serial number Average intercept of grains (μm) Example 1 38.6 Example 2 38.9 Example 3 39.3 Example 4 39.9 Comparative Example 1 63.8 Comparative Example 2 65.2 Comparative Example 3 65.8 Comparative Example 4 66.3 .
[0078] From the estimation results in Table 4, it can be seen that the Ag-NiCr alloy functional layers in Examples 1-4 of the present invention have a smoother crystal distribution, a more uniform grain distribution, and a finer grain size.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on the glass substrate surface; characterized in that: The film layer includes, from the glass substrate outward, a first silicon nitride dielectric layer with a thickness of 20-30nm, a second seed protection layer with a thickness of 10-15nm, a third nickel-chromium absorption layer with a thickness of 1-2nm, a fourth Ag-NiCr alloy functional layer with a thickness of 7-12nm, a fifth nickel-chromium absorption layer with a thickness of 1-2nm, a sixth seed protection layer with a thickness of 5-10nm, and a seventh silicon nitride dielectric layer with a thickness of 30-50nm; Wherein, the fourth Ag-NiCr alloy functional layer is formed in a vacuum degree not less than 5*10 -6 In a vacuum environment of mbar, a first silver layer with a thickness of 3-5 nm, a nickel-chromium partition layer with a thickness of 1-2 nm and a second silver layer with a thickness of 3-5 nm, which are sequentially magnetron sputtered, are heat treated at a temperature of 680-720°C for 5-8 min, and the prepared alloy material layer is cooled at a cooling rate of 60-80°C / min.
2. According to claim 1, the Ag-NiCr alloy high-transmittance tempered low-emissivity coated glass is characterized in that: The second seed protection layer is a zinc oxide layer or a titanium oxide layer.
3. According to claim 1, the Ag-NiCr alloy high-transmittance tempered low-emissivity coated glass is characterized in that: The sixth protective seed layer is an AZO layer.
4. The Ag-NiCr alloy high-transmittance tempered low-emissivity coated glass according to claim 1, characterized in that: When the fourth Ag-NiCr alloy functional layer is prepared by magnetron sputtering, the vacuum degree of the vacuum environment is not less than 3*10 -6 mbar.
5. The Ag-NiCr alloy high-transmittance tempered low-emissivity coated glass according to claim 1, characterized in that: The heat treatment temperature is 690-700°C, the time is 5-6 minutes, and the cooling rate is 65-75°C / min.
6. The Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass according to any one of claims 1 to 5, characterized in that: The thickness of the first silicon nitride dielectric layer is 22-28 nm.
7. The Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass according to any one of claims 1 to 5, characterized in that: The thickness of the second seed protection layer is 11-13 nm.
8. The Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass according to any one of claims 1 to 5, characterized in that: The thickness of the fourth Ag-NiCr alloy functional layer is 8-10 nm.
9. The Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass according to any one of claims 1 to 5, characterized in that: The thickness of the sixth seed protection layer is 6-8 nm.
10. The Ag-NiCr alloy high-transmittance temperable low-emissivity coated glass according to any one of claims 1 to 5, characterized in that: The thickness of the seventh silicon nitride dielectric layer is 35-45 nm.
Citation Information
Patent Citations
High-permeability, tempered and low-radiation coated glass and manufacturing method thereof
CN101767939A
Silver-gray high-transmission low-radiation coated glass
CN201842773U
Reinforced-type single-silver high-transmission low-radiation coated glass capable of being machined in different places
CN202608166U
Coated article including low-emissivity coating, insulating glass unit including coated article, and / or methods of making the same
CN103492337A
Tempering low-emissivity coated glass containing silver alloy
CN103802379A